Long-term survival outcome of laparoscopic staging surgery for endometrial cancer in Taiwanese experience - Chyi-Long Lee; Kuan-Gen Huang; Pei-Ju Wu; Pei-Shan Lee; Chih-Feng Yen (Elsevier, 2014)
Objective: This study aims to evaluate the long-term safety and efficacy of laparoscopic staging surgery (LSS) for endometrial cancer in Taiwanese women. Materials and Methods: This is a longitudinal study of prospectively registered 105 patients who underwent LSS for endometrial cancer between June 1995 and June 2008. Results: The mean duration of surgery was 186.8 minutes, and the mean intraoperative blood loss was 220.38 mL. The median number of retrieved pelvic lymph nodes was 18. The intraoperative complication rate was 4.8%, including two cases of ureteral injury and one case each of bladder injury, bowel injury, and vascular injury. No patient required conversion to laparotomy. During the median follow-up of 55.3 months, six cases of recurrence (5.7%) and three tumor-related deaths (2.9%) were recorded. The 5-year disease-free survival and the overall survival were 93.39% and 98.05%, respectively. Conclusion: The study revealed favorable perioperative outcomes and better long-term survival than reported in the Taiwan Cancer Registry, and similar good surgical results to those reported in the Western studies. Therefore, LSS by experienced surgeons for endometrial cancer is a feasible and efficacious alternative to laparotomy.